2010
DOI: 10.1016/j.jtcvs.2009.11.003
|View full text |Cite
|
Sign up to set email alerts
|

Functional mitral stenosis after surgical annuloplasty for ischemic mitral regurgitation: Importance of subvalvular tethering in the mechanism and dynamic deterioration during exertion

Abstract: Objective Diastolic subvalvular mitral leaflet tethering by left ventricular remodeling that restricts leaflet opening in the presence of annular size reduction by surgery for ischemic mitral regurgitation potentially causes functional mitral stenosis in the absence of organic leaflet lesions. Exercise, known to worsen systolic tethering and ischemic mitral regurgitation, might also dynamically exacerbate such mitral stenosis by increasing tethering. This study evaluates the mechanism and response of such mitr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

6
76
3

Year Published

2013
2013
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 80 publications
(85 citation statements)
references
References 25 publications
6
76
3
Order By: Relevance
“…However, Kubota et al observed the presence of functional MV stenosis even in patients whose annular size was not aggressively reduced during RMA (i.e., those who did not undergo downsizing of the annulus). 10 Likewise, Rubino et al reported no significant difference in size of the annuloplasty ring implanted during the RMA procedure between patients with and without a postoperative mean mitral gradient ≥5 mmHg (25.8±1.1 vs. 25.4±1.4 mm; P=0.06). Furthermore, despite a higher frequency of 24-mm annuloplasty rings implanted in our series, the MV gradient value observed in this study was quite consistent with that noted in previous studies.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…However, Kubota et al observed the presence of functional MV stenosis even in patients whose annular size was not aggressively reduced during RMA (i.e., those who did not undergo downsizing of the annulus). 10 Likewise, Rubino et al reported no significant difference in size of the annuloplasty ring implanted during the RMA procedure between patients with and without a postoperative mean mitral gradient ≥5 mmHg (25.8±1.1 vs. 25.4±1.4 mm; P=0.06). Furthermore, despite a higher frequency of 24-mm annuloplasty rings implanted in our series, the MV gradient value observed in this study was quite consistent with that noted in previous studies.…”
Section: Discussionmentioning
confidence: 94%
“…9 In addition, Kubota et al demonstrated that subvalvular tethering caused by LV remodeling is the primary mechanism of functional MV stenosis at the leaflet tip level. 10 These findings led us to examine which patients will be placed at risk for developing an increased MV gradient following RMA. Furthermore, it remains unknown whether postoperative functional MV stenosis following RMA has an effect on long-term clinical outcome.…”
mentioning
confidence: 99%
“…The occurrence of functional mitral stenosis after restrictive MVA has not been well studied despite its relatively high incidence (9-54%) [8,12,14]. Importantly, recent findings show that PPG can independently predict elevated systolic PAP during exercise as well as reduced 6MWT distance [4][5][6][7], which is a powerful predictor of morbidity and mortality in patients with heart failure [5,8]. Thus, elevated resting peak mitral gradients correlate well with functional mitral stenosis and could serve as a good predictor of poor functional capacity [5].…”
Section: Discussionmentioning
confidence: 99%
“…Restrictive mitral valve annuloplasty (MVA) combined with coronary artery bypass grafting (CABG) is a traditional procedure for the surgical management of CIMR [1,2]. Although restrictive MVA can reduce the risk of recurrence of mitral regurgitation (MR), it is intuitive that it may cause functional mitral stenosis, leading to higher transmitral peak pressure gradient (PPG) and pulmonary arterial pressure (PAP) and, indeed, several reports in literature support this concept [3][4][5][6]. Recent studies suggest that resting PPG is an independent predictor of increased systolic PAP during exercise, and that a PPG ≥ 13 mmHg is the best predictor of poor performance on the 6-minute walk test (6MWT) distance [4][5][6][7].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation